PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN DIORAMA TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Ismatullah Aripin; Hilman Hilmawan; Rahmatika Layyinah; Andika; Violita Rizkiya Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by diorama media on the science learning outcomes of fifth-grade elementary school students. The study employed a quasi-experimental method using a nonequivalent control group design involving an experimental class and a control class. The participants consisted of 60 fifth-grade students at SDN Cimahi 01, Cicantayan District, Sukabumi Regency, with 30 students in each class. Data were collected through pretest and posttest instruments and analyzed using the N-Gain test, Shapiro-Wilk normality test, Levene’s homogeneity test, and Independent Sample T-test. The results showed that the average score of the experimental class increased from 75.7 to 85.3, while the control class increased from 74.1 to 76.1. The N-Gain value of the experimental class was 0.381 (moderate category), whereas the control class obtained 0.104 (low category). Furthermore, the Independent Sample T-test produced a significance value of 0.00 (<0.05), indicating that the Problem Based Learning model assisted by diorama media had a significant effect on students’ science learning outcomes. Therefore, the implementation of the Problem Based Learning model supported by diorama media can serve as an effective instructional alternative to improve science learning outcomes in elementary schools, although its effectiveness should be further optimized through more consistent and sustainable implementation.